TECHNOLOGICAL BASICS OF PRODUCING SODIUM SULPHATE BY CONVERSING SODIUM CHLORIDE IN THE AQUEOUS WITH AMMONIUM SULPHATE - Djurayeva, Gulnora; Kamolov, Buri (Innovatsion texnologiyalar, 2024)
The ternary system and the quaternary system were studied by the isothermal method at 100˚ C in order to substantiate the process of conversion of sodium chloride with ammonium sulfate at elevated temperatures. The process of filtering the pulp which was formed in the processes of obtaining sodium sulfate and ammonium chloride by converting sodium chloride with ammonium sulfate has been studied. A technological scheme for the production of sodium sulfate and ammonium chloride by the conversion of sodium chloride with ammonium sulfate has been developed.